2021
DOI: 10.3390/cells10020268
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Type 2 Diabetes Differently Impacts on the Select Functions of Bone Marrow-Derived Multipotent Stromal Cells

Abstract: Bone marrow-derived multipotent stromal cells (BMMSCs) represent an attractive therapeutic modality for cell therapy in type 2 diabetes mellitus (T2DM)-associated complications. T2DM changes the bone marrow environment; however, its effects on BMMSC properties remain unclear. The present study aimed at investigating select functions and differentiation of BMMSCs harvested from the T2DM microenvironment as potential candidates for regenerative medicine. BMMSCs were obtained from Zucker diabetic fatty (ZDF; an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In contrast, BM-MSCs cultured under high glucose (HG) [ 38 ] or other diabetes simulation conditions such as a combination of HG and palmitic acid [ 39 ] or advanced glycated endproducts (AGEs) [ 40 ] showed significantly lower proliferation capacities. Such studies usually use nonphysiological high concentrations of glucose [ 41 ] and may not fully replicate the T2DM microenvironment that entails hyperglycaemia as well as high levels of AGEs, reactive oxygen species (ROS), hyperlipidaemia, hyperinsulinemia and inflammatory cytokines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BM-MSCs cultured under high glucose (HG) [ 38 ] or other diabetes simulation conditions such as a combination of HG and palmitic acid [ 39 ] or advanced glycated endproducts (AGEs) [ 40 ] showed significantly lower proliferation capacities. Such studies usually use nonphysiological high concentrations of glucose [ 41 ] and may not fully replicate the T2DM microenvironment that entails hyperglycaemia as well as high levels of AGEs, reactive oxygen species (ROS), hyperlipidaemia, hyperinsulinemia and inflammatory cytokines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vascular components within the skeletal system play a vital role in regulating bone metabolism by facilitating the necessary supply of nutrients and biochemical factors, mobilizing bone progenitor cells, and balancing osteogenesis and osteolysis [119]. Diseased conditions such as DM have been shown to negatively impact the expression of angiogenesis-related genes in the skeletal system and impair BMSCs and pericyte functionality, leading to pro-angiogenic dysfunction [120][121][122]. T1DM mice demonstrated vascular lesions in bone, especially damage to type H blood vessels, which are responsible for coupling vascularization with osteogenesis [123], while the reduced microvascular blood flow in T2DM patients was notably linked to elevated cortical bone porosity [124].…”
Section: Mtor In Bone Vascularitymentioning
confidence: 99%
“…Our result presented the similarity to Wang et al (2013) research which demonstrated the high glucose condition caused increase the growth of MSCs but decrease MSCs mineralization on mBM-MSCs derived from C57BL/6 mice. Moreover, Ribot et al (2021) study of rat BM-MSCs derived from diabetes type II rat model, the normoglycemic condition showed that despite cultured in normoglycemic condition, rat BM-MSCs still expressed elevated reactive oxygen species (ROS) level due to diabetes type II environment permanently affected cellular ROS production. In addition, elevated level of ROS in MSCs were known to inhibit the osteogenic differentiation (Chen et al, 2008;Denu and…”
Section: Discussionmentioning
confidence: 99%